Response of a Two-Degree-of-Freedom Vibration System with Rough Contact Interfaces - Zhiqiang Huang; Xun Peng; Gang Li; Lei Hao (Shock and Vibration)
This paper is focused on the influence of the rough contact interfaces on the dynamics of a coupled mechanical system. For this purpose, a two-degree-of-freedom model of a coupled seismic-vibrator-rough-ground system is proposed with which the nonlinear vibration properties are analyzed. In this model, the force-deflection characteristic of the contact interfaces is determined by finite element analysis. By analyzing the undamped free vibration, it was found that the variation of the second-order natural frequency with amplitude increases with rougher contact interfaces; however, the amplitude has little influence on the first-order natural frequency of the system. For the harmonic excited analysis, the jump frequencies and hysteretic region both decrease with rougher contact interfaces. Moreover, it is inferred from the bifurcation diagrams that, increasing the excitation force, the system can bring about chaotic motions on rough contact interfaces.